Incorporation of Carbon Quantum Dots into Cobalt Hydroxide for Supercapacitor Application - Thakur, Govinda; Pandey, Barsha; Khadka, Netra Bahadur; Sharma, Mohan; Chuwain Subedi, Kushal; Dahal, Babina; Dahal, Bipeen; Subedi, Subhangi (Journal of Nepal Chemical Society, 2026)
The rapid depletion of non-renewable resources has stepped up the pursuit globally for effective and sustainable sources of energy. Herein, cobalt hydroxide [Co(OH)₂] incorporated with carbon quantum dots (CQDs) was synthesized via a single-step hydrothermal method and characterized for supercapacitor investigations. Structural characterization through X-ray diffraction (XRD) confirmed the crystallinity of cobalt hydroxide as well as the successful incorporation of CQDs without inhibiting its crystal structure. Scanning electron microscopy (SEM) confirmed the well-defined morphology of pure as well as composite material, whereas energy-dispersive X-ray (EDX) confirmed the anticipated elemental composition. Electrochemical behavior was analyzed by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and Electrochemical impedance spectroscopy (EIS). The potential window of pure Co(OH)₂ was 0.6 V, with a specific capacitance of 800 F g-1 at 1 A g-1, which declined to 350 F g-1 at 10 A g-1. Notably, after the addition of CQD, the area of CV increased, and the optimized composite, Co(OH)₂/CQD (3), achieved a capacitance of 1300 F g-1 at 1 A g-1 and maintained 670 F g-1 at 10 A g-1. The Ragone plot confirmed superior performance of the material with energy density up to 65 W h kg-1 and the power density of 4.044 kW kg-1. The composite also retained 90.2% of the initial capacitance after 5000 repetitive charge-discharge cycles, showing excellent cycling stability. These findings highlight the potential of Co(OH)₂/CQD composites as a high-performance material for supercapacitors, offering a promising path to sustainable energy storage technology.